PERAN, PELUANG, DAN TANTANGAN PEMANFAATAN CHATGPT DALAM PEMBELAJARAN BAHASA INDONESIA DI ERA DIGITAL - Dafittra, Fernanda; Rakhmawati, Ani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of artificial intelligence (AI) is beginning to be utilized in the field of education. One AI platform that has the potential to support Indonesian language learning is ChatGPT. The purpose of this study is to examine the role, opportunities, and challenges of utilizing ChatGPT in Indonesian language learning in the digital era. This study uses a qualitative method with a descriptive analysis approach. The data in this study are written excerpts containing information about the role, opportunities, and challenges of using AI in learning. The data sources for this study are books, Sinta-indexed articles, and articles in national journals related to the use of AI. The data collection technique in this study used a literature review. Meanwhile, the data analysis technique used three main stages: data reduction, data presentation, and conclusion drawing. The validity of the research data used source triangulation. The results of this study indicate that ChatGPT has a role as an interactive media, a digital learning assistant, and a tool for developing language skills. In addition, ChatGPT has the potential to support personalized learning, improve digital literacy, support flexible learning, and lighten the workload of teachers. Despite its potential and potential, ChatGPT also faces challenges in its implementation, including dependence on technology, academic ethics, access gaps, and issues of information validity. Therefore, ChatGPT must be used wisely, ethically, and responsibly.